Young Entrepreneurs in Action : Pelatihan Minyak Urut Karo di Panti Asuhan Cinta Anak Kasih Setia Mu: Penelitian Pengabdian - Hrp, Ardhansyah Putra; Nurmairina; Enda Jerina Br Tarigan; Enelta Dian Filma; Erika Syahnum; Ester Agnes Jovanka Simamora; Febiola Natasya Simangunsong; Feli Finna Sitinjak (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training in making Minyak Urut Karo (Karo massage oil) is a form of community service activity aimed at children residing at the Cinta Anak Kasih Setia Mu orphanage. The main goal of the program is to enhance participants’ practical skills while fostering an entrepreneurial spirit. Minyak Urut Karo was chosen due to its easily accessible ingredients, simple production process, and promising market value. During the training, participants were guided step-by-step through the oil-making process and were also introduced to basic knowledge of packaging, marketing, and small business concepts. The outcomes showed that participants were able to follow the entire training process effectively and demonstrated an interest in independently developing the product. Beyond skill development, this activity also encouraged participants to gain confidence in exploring business opportunities based on local products. This initiative is expected to serve as an early step toward economic independence and instilling entrepreneurial values from a young age, especially among children living in orphanages.